Transformation of Learning Through the Combination of AI and Immersive Learning Experiences - Nadhira Mazaya Putri; Fazhar Restu Fauzi; Arie Susanty (SEAMEO SEAMOLEC, 2023)
Rapid advancements in Artificial Intelligence (AI) have opened new horizons for educational transformations. This research investigates the transformative potential of combining AI and immersive learning experiences to enhance the educational landscape. Employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model as a developmental framework, this study delves into the fusion of AI technologies and immersive learning environments. A comprehensive literature review supports the design phase, exploring the integration of AI in the development of immersive learning materials. Findings from this research illuminate the profound impact of synergizing AI and immersive experiences on the learning process. The practical and pedagogical implications of this study contribute valuable insights to the ongoing discourse on innovative learning strategies. This research is poised to inform the development of educational practices that harness the synergies between AI and immersive learning, ultimately fostering more effective and engaging learning environments.